The Hippocampal Vulnerability to Herpes Simplex Virus Type I Infection: Relevance to Alzheimer’s Disease and Memory Impairment - Yong, Shin Jie; Yong, Min Hooi; Teoh, Seong Lin; Soga, Tomoko; Parhar, Ishwar; Chew, Jactty; Lim, Wei Ling (Frontiers in Cellular Neuroscience, 2021)
Herpes simplex virus type 1 (HSV-1) as a possible infectious aetiology in Alzheimer’s disease (AD) has been proposed since the 1980s. The accumulating research thus far continues to support the association and a possible causal role of HSV-1 in the development of AD. HSV-1 has been shown to induce neuropathological and behavioural changes of AD, such as amyloid-beta accumulation, tau hyperphosphorylation, as well as memory and learning impairments in experimental settings. However, a neuroanatomical standpoint of HSV-1 tropism in the brain has not been emphasized in detail. In this review, we propose that the hippocampal vulnerability to HSV-1 infection plays a part in the development of AD and amnestic mild cognitive impairment (aMCI). Henceforth, this review draws on human studies to bridge HSV-1 to hippocampal-related brain disorders, namely AD and aMCI/MCI. Next, experimental models and clinical observations supporting the neurotropism or predilection of HSV-1 to infect the hippocampus are examined. Following this, factors and mechanisms predisposing the hippocampus to HSV-1 infection are discussed. In brief, the hippocampus has high levels of viral cellular receptors, neural stem or progenitor cells (NSCs/NPCs), glucocorticoid receptors (GRs) and amyloid precursor protein (APP) that support HSV-1 infectivity, as well as inadequate antiviral immunity against HSV-1. Currently, the established diseases HSV-1 causes are mucocutaneous lesions and encephalitis; however, this review revises that HSV-1 may also induce and/or contribute to hippocampal-related brain disorders, especially AD and aMCI/MCI.